Evaluating Heme-Oxygenase-1 and Bilirubin Concentration from the Recovered and Glomerulonephritis Patients from Lady Reading Hospital (LRH) District Peshawar, Pakistan - Bibi Hajira Ishaq, Mohammad Iqbal, Sundal Aziz, Faridullah Shah, Hafiz Mahmood Azam, Aziz U Rehman, Zahoor Ahmed, Alia Mushtaq, Asia Noureen (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Different studies suggest the defending role of bilirubin and “heme-oxygenase-1(HO-1)” in inflammatory illnesses, but there are limited studies that evaluate these two in recovered patients. Methods: Therefore, the current study evaluates the bilirubin and HO-1 in patients who suffered from glomerulonephritis and recovered (6 months ago) from the glomerulonephritis and control group. Findings &Practical Implication: After obtaining the informed consent, sample of the urine and blood were collected from the Lady Reading Hospital (LRH) in district Peshawar, Pakistan. After analysis, it was established that HO-1 and bilirubin levels were found to be greater in participants with kidney infections (HO-1:3.220 and bilirubin: 5.536) compared to the control group (HO-1:1.402 and bilirubin: 2.637). Surprisingly, the levels of HO-1 and bilirubin were in upper limits in the recovered individuals (HO-1:2.333 and bilirubin 4.295) compared to the control group but lower in the glomerulonephritis patients. Further, it was found from the regression analysis that there was no association among the level of HO-1 and bilirubin of the subjects in all study groups. Conclusion: From the current study, it was concluded that there was no effect of HO-1 on the level of bilirubin in blood plasma. Moreover, it was still unknown why HO-1 and bilirubin levels were in upper limits in the recovered patients. Future research should focus on the levels of HO-1 and bilirubin in recovered patients to see whether they indicate any underlying medical issues. Keywords: Heme-oxygenase-1; Bilirubin; Glomerulonephritis; Recovered patients